2010
DOI: 10.1016/j.jcms.2010.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical aspects of a 2.0-mm locking plate system for mandibular fracture surgery

Abstract: SUMMARY. Purpose: The use of a 2.0-mm locking plate system was evaluated in mandibular surgery. Patients and methods: 53 patients (42 male, 11 female) with a total of 56 mandibular fractures were treated with a 2.0-mm mini-locking-plate system and retrospectively examined. Gender, age, cause of fracture, surgical access, classification of fractures, osteosynthesis, postsurgical findings and complications were evaluated. Results: Assault in male patients (mean age 31) was the most common aetiological factor. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1
11

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 22 publications
(32 reference statements)
1
14
1
11
Order By: Relevance
“…We did not report any case of wound dehiscence postoperatively in any of our group while Sauerbier et al 24 reported 7.5% of wound dehiscence with locking plate in their study because patients had a positive history for either alcohol or tobacco use or for both but in our study, some patients do have positive history of either alcohol or tobacco use or both but because of their compliance and no reported case of infection, we did not observe any case of wound dehiscence. None of our patient reported with hardware failure in any group, as we did not observe any case of infection and loosening of screws which promotes inflammation, which is in agreement with Collins et al, 25 while Nayak et al 17 reported 1% and 12% patients with plate fracture and 4% and 28% with loosening of screws in locking and non-locking group respectively and Saikrishna et al 22 reported 5% and 15% patients with hardware failure in locking and non-locking group respectively.…”
Section: Discussioncontrasting
confidence: 53%
“…We did not report any case of wound dehiscence postoperatively in any of our group while Sauerbier et al 24 reported 7.5% of wound dehiscence with locking plate in their study because patients had a positive history for either alcohol or tobacco use or for both but in our study, some patients do have positive history of either alcohol or tobacco use or both but because of their compliance and no reported case of infection, we did not observe any case of wound dehiscence. None of our patient reported with hardware failure in any group, as we did not observe any case of infection and loosening of screws which promotes inflammation, which is in agreement with Collins et al, 25 while Nayak et al 17 reported 1% and 12% patients with plate fracture and 4% and 28% with loosening of screws in locking and non-locking group respectively and Saikrishna et al 22 reported 5% and 15% patients with hardware failure in locking and non-locking group respectively.…”
Section: Discussioncontrasting
confidence: 53%
“…Published by Elsevier Ltd. All rights reserved. ଝ in the management of these fractures due to the advantages of increased stability, shorter surgical time and the preservation of bony perfusion [19]. The 2.0-mm locking plates present a stability that is three times higher than conventional miniplates, which is because the fixation method is analogous to external fixation; the screws form together with the plate and cortical bone to construct a frame [14].…”
Section: Introductionmentioning
confidence: 99%
“…Isto significa que, mesmo que um parafuso seja inserido num espaço do traço de fratura, o afrouxamento do parafuso não vai ocorrer (Raveh et al, 1987;Ellis III, 1999;Graham, 2002;Ribeiro Junior et al 2010;Sauerbier et al, 2010;Singh, 2010;Kumar et al, 2013;Yang;Patil, 2015).…”
Section: Resultsunclassified
“…Mais recentemente, placas locking 2,0 mm vem sendo utilizadas no tratamento das fraturas mandibulares, sendo descritas uma série de vantagens (Sauerbier et al, 2010), sendo indicadas inclusive em fraturas com potencial para complicações (Camino Junior et al, 2016).…”
Section: Lista De Figurasunclassified
See 1 more Smart Citation